الجزاء الإلاهي في الحياة الدنيا من القرءان الكريم - يوسف, نجود; ياقوتة, زينب (جامعة الوادي university of eloued, 2019)
تعابِ ىذه الدراسة جزاء الله تعالى بُ الدنيا للمطيعتُ والعصاة من خلال الاستناد إلى القرآن الكرنً الذي تناول بُ الكثتَ من آياتو ابعزاء الدنيوي.وىو موضوع بُ غاية الأبنية لارتباطو بالواقع الإنساني الفردي والاجتماعي.وقد وظفنا بُ اشتغالنا على ىذا ابؼوضوع منهجا استقرائيا وآخر برليليا عمدنا من خلابؽما إلى تتبع الآيات القرآنية التي تطرقت إلى نوع ىذا ابعزاء من جهة، وبرليلها بتفستَىا وشرحها جزئياتها واستنباط ما أمكن استنباطو من نتائج، لنخلص بُ الأختَ إلى أن ابعزاء الدنيوي وإن كان ينزل درجة عن ابعزاء الأخروي إلا أن القرآن الكرنً نبو عليو بؼا لو من أبنية وآثار بُ تصحيح عقيدة وسلوك ابؼسلم. Firstly, our stydy deals with penalty of allah for his human (obedient_desobedient) by depending and relying on his holy book which is the holy quran . However , the quran contained many of verses that talk about world and life penatly (punishment), also this is such an important subject that deals with human and society in their real life . Moreover, we have employed in this field the analytical method through this verses that describes our subject. Finaly, we have concluded by the peanalty’s in life is not eqaul and the same of penalty’s after death, but generally our quran warned and has notifed that the penalty’s (punishment) has its own goals and characteristics in correcting the peoples doctrine and thier behaviour .
ليسانس